2006
DOI: 10.1089/jir.2006.26.235
|View full text |Cite
|
Sign up to set email alerts
|

Cell to Cell Contact Through ICAM-1-LFA-1 and TNF-αSynergistically Contributes to GM-CSF and Subsequent Cytokine Synthesis in DBA/2 Mice Induced by 1,3-β-D-Glucan SCG

Abstract: SCG is a major 6-branched 1,3-beta-D-glucan in Sparassis crispa Fr. showing antitumor activity. We recently found that the splenocytes from naive DBA/1 and DBA/2 mice are potently induced by SCG to produce interferon- gamma (IFN-gamma), tumor necrosis factor-alpha (TNF-alpha), granulocyte-macrophage colony-stimulating factor (GM-CSF), and interleukin-12p70 (IL-12p70), and that GM-CSF plays a key biologic role among these cytokines. In this study, we investigated the contribution of cell-cell contact and solubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…Of the 6 cell membrane receptors that were blocked by key mAbs to prevent Sophy β-glucan-induced DNA synthesis in cultured PBMCs, CD11a, CD54 and HLAclass II are widely expressed in all lymphoid and myeloid cells and play an important role in the regulation of various immune responses, such as cell proliferation/differentiation and adhesion, and immunoregulatory cytokine production (21,38). In this study, the cell-to-cell contact mechanism(s) underlying the DNA synthesis induced in PBMCs by Sophy β-glucan was investigated using CD11a, CD54 and HLA-class II key mAbs in an inhibition test, because it has been reported previously that cell-to-cell contact involving CD11a (LFA-1), CD54 (ICAM-1) and other cell surface antigens is an essential step in the induction of cytokines, such as granulocyte/macrophage-colony stimulating factor (GM-CSF) and IFN-γ by 6-branched 1,3-beta-Dglucan (SCG) derived from Sparassis crispa (18).…”
Section: Immunological Actions Of Sophy β-Glucanmentioning
confidence: 99%
“…Of the 6 cell membrane receptors that were blocked by key mAbs to prevent Sophy β-glucan-induced DNA synthesis in cultured PBMCs, CD11a, CD54 and HLAclass II are widely expressed in all lymphoid and myeloid cells and play an important role in the regulation of various immune responses, such as cell proliferation/differentiation and adhesion, and immunoregulatory cytokine production (21,38). In this study, the cell-to-cell contact mechanism(s) underlying the DNA synthesis induced in PBMCs by Sophy β-glucan was investigated using CD11a, CD54 and HLA-class II key mAbs in an inhibition test, because it has been reported previously that cell-to-cell contact involving CD11a (LFA-1), CD54 (ICAM-1) and other cell surface antigens is an essential step in the induction of cytokines, such as granulocyte/macrophage-colony stimulating factor (GM-CSF) and IFN-γ by 6-branched 1,3-beta-Dglucan (SCG) derived from Sparassis crispa (18).…”
Section: Immunological Actions Of Sophy β-Glucanmentioning
confidence: 99%
“…were induced by SCG in adherent splenocytes alone; on the other hand, IFN-γ induction by SCG required adherent cell-T cell interaction (15). In a previous study, we showed that the leukocyte recovery in CY-treated mice was different for different cell populations, such as granulocytes, macrophages, natural killer cells, B cells and T cells (11,30).…”
Section: Discussionmentioning
confidence: 89%
“…Recently, we found that GM-CSF is a key molecule for cytokine induction by β-glucan, and that GM-CSF production is specifically induced in DBA/2 mice in vitro (12,14,15). In this study, we investigated the key factors in the cytokine induction by SCG in CY-treated mice, and found that GM-CSF plays an important role in this system.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations